2010
DOI: 10.1158/1078-0432.ccr-10-0068
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nanoparticulate Formulation of Arsenic Trioxide with Enhanced Therapeutic Efficacy in a Murine Model of Breast Cancer

Abstract: Purpose: The clinical success of arsenic trioxide (As 2 O 3 ) in hematologic malignancies has not been replicated in solid tumors due to poor pharmacokinetics and dose-limiting toxicity. We have developed a novel nanoparticulate formulation of As 2 O 3 encapsulated in liposomal vesicles or "nanobins" [(NB(Ni, As)] to overcome these hurdles. We postulated that nanobin encapsulation of As 2 O 3 would improve its therapeutic index against clinically aggressive solid tumors, such as triple-negative breast carcinom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
105
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 37 publications
10
105
0
1
Order By: Relevance
“…Triple-negative MDA-MB-231-mCherry breast cancer cells (1 Â 10 6 ) in 100% Matrigel (BD Bioscience) were injected into the ducts of both 4th mammary glands of 4-to 5-week-old female athymic nu/nu mice (Harlan Laboratories) as described (33). To characterize the metastatic phenotype of this orthotopic model, mice were euthanized at 2-week intervals from 2 to 10 weeks after tumor inoculation (6-8 mice/time point).…”
Section: Orthotopic Model Of Metastatic Breast Cancermentioning
confidence: 99%
“…Triple-negative MDA-MB-231-mCherry breast cancer cells (1 Â 10 6 ) in 100% Matrigel (BD Bioscience) were injected into the ducts of both 4th mammary glands of 4-to 5-week-old female athymic nu/nu mice (Harlan Laboratories) as described (33). To characterize the metastatic phenotype of this orthotopic model, mice were euthanized at 2-week intervals from 2 to 10 weeks after tumor inoculation (6-8 mice/time point).…”
Section: Orthotopic Model Of Metastatic Breast Cancermentioning
confidence: 99%
“…Previously, Choi HSC et al [4,5] reported that Fan has Anti-inflammatory effects. Zhang YH et al [8,9] also reported that Fan inhibited rat aortic vascular smooth muscle cell proliferation and cell cycle progression through inhibition of ERK1/2 activation and c-fos expression. However, this is the first report to demonstrate that Fan induced apoptosis in breast cancer xenograft and Fan could be consider as a potential drug for future breast tumor therapy.…”
Section: Fan Induced Apoptosis In Nude Mice Xenograftmentioning
confidence: 97%
“…Nerve growth factor has been used as a target in curing breast cancer in the form of anti-NGF antibodies or small interfering RNA against NGF displaying inhibition of tumor growth and metastasis [7]. Nanobin encapsulation of As 2 O 3 improves the pharmacokinetics and antitumor efficacy in breast cancer in vivo [8,9]. Based on the progress of anti-tumor therapeutics, we selected Fan, an efficient component of Stephaniae tetrandrine to test its potential effect on breast cancer.…”
mentioning
confidence: 99%
“…It has been shown that arsenic directly binds to PML-RARa fusion proteins and then induces its protein degradation, resulting in induced cell differentiation and apoptosis (Zhang et al 2010). Moreover, As 2 O 3 is also being newly applied for other forms of tumor and diseases for clinical treatment (Bobe et al 2006;Ahn et al 2010). However, little is known about the mechanisms underlying arsenic-induced anticancer effects in patients, because As 2 O 3 can be quickly transformed into mono-and dimethylated forms in human and animals after the injection (Vahter and Marafante 1983;Wang et al 2004;Drobna et al 2009).…”
Section: Introductionmentioning
confidence: 99%